Pengembangan Video Animasi “Si Raja Kecil di Tanah Batak” Siswa Kelas V Mis Kesuma LKMD - Mutiara Rahmah; Arrini Shabrina Anshor (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to develop an educational animation video entitled "Si Raja Kecil di Tanah Batak" to enhance students’ learning interest in understanding the values of Pancasila. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were fifth-grade students at MIS Kesuma LKMD, totaling twenty two students. The results of the validation process indicated that the developed media was highly valid, with a media expert validation score of 93.33% and a material expert score of 86%. The practicality test yielded a score of 84.54%, indicating that the media is highly practical for daily classroom learning activities. Furthermore, the effectiveness of the animation video in increasing students’ interest in learning Pancasila values reached 82.87%. Therefore, the animation video "Si Raja Kecil di Tanah Batak" is proven to be valid, practical, and effective as a learning medium for supporting the understanding of Pancasila values at the elementary school level.